(untitled) (Ágora Journal, 2024)
With this work we analyze a poem by Bruno de Menezes, a modernist from the Amazon, written in the 1920s. This poem is analyzed by historiography and literary criticism as a “party” of black people in which there is a perception of Afro characteristics. -Brazilian. However, our proposal aims to understand the narration of the episode as a spiritual “ritual” or Afro-Amazonian religiosity that includes Catholic characteristics, religions of African origins and indigenous origins. Thus, by reconstructing the episode not as people dancing, but people in trance, we better understand the culture, power and identity relations of this black Amazonian represented by the author. To this end, the author’s biography was reconstructed, his sociability network was understood and the poem was analyzed in light of the Amazonian reality of the 1920s.